The perceptions and practices of the integration of knowledge amongst the academics of International Islamic University Malaysia (IIUM) - Hussien, Suhailah; Mamat, Arifin; Abdallah, Siraje, S. (ISTAC, 2018)
International Islamic University of Malaysia`s (IIUM) vision and mission is its commitment to the integration of values with the modern fields of knowledge. Today, Islamization and integration have emerged as niche areas of the IIUM. There are various phases and orientations of the implementation of Islamization of knowledge (IOK) at the IIUM. The study is important as it helps IIUM to identify and monitor the areas of specialization that need to be improved with regards to the Islamic values integration. Thus, the aim of the paper is to investigate the perceptions and practices of IIUM academics in their efforts to do IOK. The study is exploratory in nature and involves focus group discussion (FGD) with six kulliyyahs namely Kulliyyah of Engineering, ICT, Laws (AIKOL), Economics (ENM), IRKHS, and Science. Each FGD lasted between one to two hours, and involved about five to six lecturers from each Kulliyyah. Two broad themes were generated from the data, which are perceptions and practices of IOK. The general findings of the study reveal that IIUM academics perceive and practice IOK differently according to their background and various specializations. IIUM academics generally perceive IOK as an important endeavor though challenging, yet differ in their views of its success. Meanwhile, the practices of IOK involve content, teaching and learning, materials, research and publication, assessment, and students. IIUM academics face many challenges in implementing IOK such as lack of resources, lack of academics involvement in IOK activities, and lack of Islamic knowledge to integrate technical, scientific and conventional knowledge. The study suggests that with proper and continuous support from the University, IOK could be implemented more effectively.